Securing personal freedom through institutions: the role of electoral democracy and judicial independence - Niclas Berggren; Jerg Gutmann (European Journal of Law and Economics, 2020)
We investigate empirically how electoral democracy and judicial independence relate to personal freedom. While judicial independence is positively and robustly related to personal freedom in all its forms, electoral democracy displays a robust, positive relationship with only two out of seven types of personal freedom (freedom of association, assembly and civil society; freedom of expression and information). Interaction terms and more refined indicators of the political system reveal that countries without elections or with only one political party benefit more from judicial independence than both democracies and multi-party systems without free elections.
Keywords: D63; D72; D78; K36; K38; P48; 340; Freedom; Democracy; Judicial independence; Political economy; Institutions